Anisotropic domain structures of Pb(Mg1/3Nb2/3)O3–PbZrO3–PbTiO3 single crystals with high ferroelectric phase transition temperature. Issue 4 (2nd February 2017) - He, Wenhui; Jiang, Tong; Li, Qiang; Xi, Xiaoqing; Yan, Qingfeng
Abstract: The anisotropic domain structures and local piezoresponse of rhombohedral Pb(Mg1/3 Nb2/3 )O3 –PbZrO3 –PbTiO3 single crystals with high ferroelectric phase transition temperature ( T FE‐FE ≥120°C) were systematically investigated by vector piezoresponse force microscopy. The typical size of labyrinthine domain pattern for [001] C sample was in the range of 100‐200 nm, revealing its relaxor feature. While the [011] C sample exhibited ordered ribbon‐shaped domain pattern with preferential alignment along <011> direction since the modulation effect of polar nanoregions. For [111] C sample, it had messy and featureless domain patterns. For as‐grown crystal, the incorporation of Zr 4+ cation in Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 system resulted in that the long‐range coulomb interactions of the charged ions in the short range order regions were weakened, leading to an increased relaxor feature. Concurrently, the incorporation of Zr 4+ cation enhanced the Pb‐B repulsion intensity, resulting in an improved T FE‐FE . Temperature‐dependent properties of as‐grown crystal exhibited good temperature stability from 30 to 120°C, indicating it is a promising material for actuator and ultrasonic transducer applications.